Fraud Hexagon Model in Detecting Fraudulent Financial Reporting in the State-Owned Enterprise Environment - Tirza Venisia Sinambela; Sri Rahayu; Riski Hernando (International Forum of Researchers and Lecturers, 2026)
This study aims to examine the effect of Fraud Hexagon Theory elements, namely stimulus/pressure, capability, collusion, opportunity, rationalization, and ego on fraudulent financial reporting in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2019–2024 period. This research employs a quantitative method with an associative approach and multiple linear regression analysis. The sample was determined using purposive sampling, resulting in 27 companies with a total of 162 observations. The results indicate that all independent variables simultaneously influence fraudulent financial reporting. Partially, stimulus/pressure and opportunity have a significant negative effect, while rationalization and ego have a significant positive effect on fraudulent financial reporting. Meanwhile, capability and collusion do not show a significant effect. These findings suggest that pressure and opportunity factors, along with rationalization and ego, play important roles in influencing the occurrence of fraudulent financial reporting.